(untitled) (Research, Society and Development, 2022)
Efforts have been made to understand possible prosodic alterations in the speech of autistic subjects. Thus, this study aims to analyze the relative duration of vowels produced by children with and without autism. The aim is to highlight any difficulties in demarcating the accent between participants with autism. For the investigation, 06 (six) male participants were selected, 03 (three) with autism and 03 (three) with typical development. The participants, all readers, are from Vitória da Conquista, BA. For analysis, a corpus of words with Brazilian Portuguese vowels in different syllabic positions was assembled. The words were inserted in sentences such as “I say_____ softly.” and presented in Power Point slides to the participants to be read and recorded in a soundproof booth. Data analysis was performed using the PRAAT software, through which the relative duration of each vowel was measured. Subsequently, we used the statistical parameter of the Coefficient of Variation and the non-parametric Kruskal-Wallis test to expand the discussion of the data. The results showed that subjects with autism show alterations in accent demarcation, which may be an indication of prosodic alterations in speech in the autistic population.